Increased 1,2-diacylglycerol content in myopathic hamster hearts at a prenecrotic stage - Okumura, K; Yamada, Y; Kondo, J; Ishida, A; Hashimoto, H; Ito, T; Ogawa, K; Kitoh, J (Life sciences (1973), 1988)
1,2-Diacylglycerol (DAG) has been suggested to be a secondary messenger. In this study, we determined the amount of 1,2-DAG in heart tissue from Syrian hamsters with hereditary cardiomyopathy at 30 days (prenecrotic stage) and 90 days of age by thin-layer chromatography with flame ionization detection (TLC-FID). Myocardial triglyceride contents were higher at 30 days of age and lower at 90 days of age compared to the levels in age-matched normal hamsters. Decreases in major species of phospholipids in hearts were observed only at 90 days of age. However, elevated 1,2-DAG content in myopathic hearts was found at 30 days of age, whereas there was no difference between the two groups at 90 days of age. It is suggested that the increase in 1,2-DAG at the prenecrotic stage is involved in the pathogenesis of the cardiomyopathy.